IMPLEMENTASI KEWIRAUSAHAAN DI PONDOK PESANTREN SIROJUT THOLIBIN MATARAM BARU LAMPUNG TIMUR - daman, Damanhuri; Yuliyanto (LPPM STAI DARUSSALAM LAMPUNG, 2023)
The purpose of this research is to determine the implementation of entrepreneurship carried out at the Sirojut Tholibin Islamic boarding school, the research method uses descriptive qualitative. The description of the research is the implementation of entrepreneurship carried out at the Sirojut Tholibin Islamic boarding school with a worship platform, where all economic activities carried out are intended to worship Allah SWT. The application of entrepreneurship is carried out, students are trained to manage economic institutions in the Sirojut Tholibin madrasah boarding school. On the other hand, the profit of the madrasah boarding school is not always an important priority, because what is instilled at the start of entrepreneurship at the boarding school is the intention to worship and simply hope for Allah's blessing, as a result the students not only have solid religious knowledge but also have an entrepreneurial spirit for their life.